1996
DOI: 10.1111/j.1365-3091.1996.tb01458.x
|View full text |Cite
|
Sign up to set email alerts
|

Field measurements of the flux and speed of wind‐blown sand

Abstract: A field experiment was conducted to measure the flux and speed of wind-blown sand under known conditions in a natural setting. The experiment, run at Pismo Beach, California, involved a tract 100 m long (parallel with the wind) by 20 m wide. The site was instrumented with four arrays of anemometers to obtain wind velocity profiles through the lower atmospheric boundary-layer, temperature probes to determine atmospheric stability and wind vanes to determine wind direction. From these measurements, wind friction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
140
2
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(157 citation statements)
references
References 19 publications
13
140
2
2
Order By: Relevance
“…First, electric forces affect the trajectories of saltating particles, as first suggested by Schmidt et al (1998) and Zheng et al (2003). Indeed, the presence of electric forces might explain the puzzling discovery that the height to which saltating particles bounce does not increase with wind speed (Greeley et al, 1996;Namikas, 2003). This is in direct contradiction with saltation theory (Bagnold, 1941;Owen, 1964), which posits that the saltation layer height should increase markedly with wind speed.…”
Section: The Effects Of Electric Forces On Saltation and Dust Liftingcontrasting
confidence: 45%
See 1 more Smart Citation
“…First, electric forces affect the trajectories of saltating particles, as first suggested by Schmidt et al (1998) and Zheng et al (2003). Indeed, the presence of electric forces might explain the puzzling discovery that the height to which saltating particles bounce does not increase with wind speed (Greeley et al, 1996;Namikas, 2003). This is in direct contradiction with saltation theory (Bagnold, 1941;Owen, 1964), which posits that the saltation layer height should increase markedly with wind speed.…”
Section: The Effects Of Electric Forces On Saltation and Dust Liftingcontrasting
confidence: 45%
“…Classical saltation theory predicts that z 50 increases strongly with shear velocity (Bagnold, 1941;Owen, 1964), which the numerical model also predicts when electric forces are not included (black circles). However, field measurements [squares (Namikas, 2003) and triangles (Greeley et al, 1996)] show that z 50 remains approximately constant with shear velocity. The inclusion of sand electrification in the numerical model (red circles) apparently resolves the discrepancy between theory and measurements.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Many studies have revealed that there is an exponential decay of mass flux with height (Dong et al, 2002b;Greeley et al, 1996;Rasmussen and Sørensen, 1999). The experiment of Dong et al (2002b) shows the sand mass flux decreases exponentially with height.…”
Section: Computational Results and Discussionmentioning
confidence: 99%
“…The experiment of Dong et al (2002b) shows the sand mass flux decreases exponentially with height. The field measurement of Greeley et al (1996) shows that there is a clear log-linear decrease in sand flux with height. Rasmussen and Sørensen (1999) used the isokinetic trap to measure the sand mass flux in a field, and there is an exponential behavior between mass flux and height.…”
Section: Computational Results and Discussionmentioning
confidence: 99%
“…Although high-speed multi-flash photography and photoelectric cell methods have been used to measure movement velocities of individual particles (Zou et al, 1994;Greeley et al, 1996), these methods prove to be only good for fairly large particles (Greeley and Iversen, 1985). It is also difficult from photographic images to interpret the velocity of sand particles at very low heights such as below 0.5 cm where the grains are too crowded, and at higher height, such as over 7 cm, where the moving grains are too few (Zou et al, 2001).…”
Section: Introductionmentioning
confidence: 99%